O uso da rede BLOCKCHAIN no mercado criativo: a gestão de direitos autorais de obras musicais no ambiente digital. - Ferreira, Ana Flávia da Costa (2020)
In the information society, creativity has become the new economic paradigm. In this scenario, the creative industry rises as an emerging sector that has intellectual capital as its main raw material and in the protection of its intangible assets, by intellectual property laws, one of the guarantees for its development. However, the advent of the Internet, which provided a greater exchange of data and information, also caused the emergence of a market for the unauthorized distribution of intellectual goods, a circumstance that required the increase of levels of copyright protection in a digital environment in order to preserve harmony between the author's monopoly and society's right to information, culture and knowledge. Nevertheless, such protection measures, and the system that manages them, remained inefficient, in addition to stimulating a greater imbalance between the right of access and the right of property of the creator, a reality that affects the very development of the market. These circumstances remained well evidenced in the music industry, which is why it became the scope of the research, being necessary to make a cut to address only the aspects related to the management of digital copyright in the phonographic market. In this perspective, the work sought to analyze how blockchain technology could contribute to the development of the creative music industry, from its use in copyright management in a digital environment. To this end, the work went in the direction of analyzing the model for collecting and distributing copyright in streaming, as well as investigating copyright management technology (DRM) and collective copyright management in Brazil. Finally, the research concluded that the use of blockchain technology in copyright management in a digital environment, when overcome some implementation obstacles, has the potential to promote a new leap in the development of the music industry through the promotion of a fair, safe and transparent remuneration for authors, providing the harmonization of antagonistic rights, such as the right of property of the creator of intellectual works and the right of society to access a particular work.